Factors related to earthquake preparedness of households based on social-cognitive theory constructs: A systematic review - Rezabeigi Davarani, Esmat; Nekoei-Moghadam, Mahmood; Khanjani, Narges; Iranpour, Abedin; Chashmyazdan, Mohammadreza; Farahmandnia, Hojjat (Frontiers in Public Health, 2023)
Background: pre-hospital emergency is a community-oriented system that responds to the medical needs of the injured or patients with acute and emergency illnesses outside of health care facilities until they are transferred to a medical center.This study aimed to explore pre-hospital emergency challenges in the face of the COVID-19 pandemic. Material and Methods: This study was conducted as a qualitative content analysis. Using purposive sampling method, data was collected through in-depth semi-structured individual interviews with 28 prehospital paramedic personnel and analyzed using Graneheim and Lundman’s conventional content analysis methods. The trial version of MAXQDA 16 software was used to manage the coding process. Results: Based on the results of data analysis and after several rounds of reviewing and summarizing the data and taking into account similarities and differences, four main categories and 10 subcategories were obtained through the content analysis method, including 1) Culture and Community, 2) Service delivery, 3) human resources, and 4) Medical equipment and supplies. Conclusion: Identifying the most important challenges for health care providers can play an important role in improving the management of the new coronavirus epidemic (COVID-19). The analysis of the challenges by managers at urban, provincial, and national levels can lead to the presentation of effective solutions to address these challenges and improve the epidemic management process in the country. As pointed out in this study, it seems that to solve some of these challenges, coordination is needed outside the health sector. Besides, the formation of the National COVID-19 Control Center can contribute to developing necessary policies and strategies for handling the pandemic.